1996
DOI: 10.1096/fasebj.10.2.8641559
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐dependent cellular cytotoxicity in HIV infections

Abstract: ADCC is an important immune effector mechanism against tumor and virus-infected cells that can be destroyed by the combined action of specific antibodies of IgG isotype against cell surface-associated antigens and effector cells, predominantly of the NK phenotype. ADCC has been shown to function in vivo in several systems. With regard to HIV, it can be readily demonstrated in vitro against the viral envelope proteins with serum and/or effector cells obtained from HIV-infected subjects. Several studies have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 5 publications
1
70
0
1
Order By: Relevance
“…The killing of virus-infected cells by ADCC involves cytotoxic cells (such as NK cells) and may contribute to elimination of the virus. [23][24][25][26] Alsmadi and Tilley 27 studied the ability of human and chimpanzee mAbs directed against cluster II overlapping epitopes of gp41, CD4 binding site, V3 loop and C5 domain of gp120 for their ability to induce ADCC. They demonstrated that mAbs directed against conserved epitopes generally exhibited ADCC activity against a broader range of HIV-1 strains than those directed against variable epitopes.…”
Section: Mechanisms Of Antibody Mediated Protectionmentioning
confidence: 99%
“…The killing of virus-infected cells by ADCC involves cytotoxic cells (such as NK cells) and may contribute to elimination of the virus. [23][24][25][26] Alsmadi and Tilley 27 studied the ability of human and chimpanzee mAbs directed against cluster II overlapping epitopes of gp41, CD4 binding site, V3 loop and C5 domain of gp120 for their ability to induce ADCC. They demonstrated that mAbs directed against conserved epitopes generally exhibited ADCC activity against a broader range of HIV-1 strains than those directed against variable epitopes.…”
Section: Mechanisms Of Antibody Mediated Protectionmentioning
confidence: 99%
“…A dysfunction of NK cells is present in the course of HIV infection, as indicated by a decrease in NK cell numbers (5)(6)(7)(8)(9) and MHC-nonrestricted (10) and Ab-dependent cell-mediated cytotoxicity (6,(11)(12)(13). In addition to their role in antiviral immunity (14 -16), NK cells produce cytokines and chemokines with antiviral activity (17,18) and IFN-␥, which may directly contribute to HIV control and lack of disease progression.…”
Section: H Uman Immunodeficiency Virus Infection Progressivelymentioning
confidence: 99%
“…Specifically, NK cells in viremic, chronically HIV-1-infected individuals have decreased natural cytotoxicity (as measured by the killing of the prototypic NK cell target K562 cell line) (38 -42) and decreased Ab-dependent cellular cytotoxicity (ADCC) (41,(43)(44)(45). However, a study by Alter et al has shown that even though viremic HIV-1 infection is associated with a reduction in NK cell numbers and a perturbation of NK cell subsets, the overall NK cell activity is increased (46).…”
mentioning
confidence: 99%